UPAYA MENINGKATKAN KEMAMPUAN MENULIS TEKS BERITA PADA SISWA SMP NEGERI 5 SELUAS - Sari, Trileviana; Syam, Christianto; Syambasril, Syambasril (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was backgrounded based on the observation that the 8th-grade students of SMPN 5 Seluas have low skills in writing news text. This is influenced by internal factors such as having low motivation, having difficulties in expressing ideas, as well as external factors such as classroom tended to be teacher-centered, and the tendency to neglect affective and psychomotor aspects in the learning process. Therefore, these results in writings that lack variation for the students only write based on the result of memorizing a set of facts instead of finding their own experience in class. This class action research was carried out in two cycles, of which each comprised planning, acting, observing, and reflecting. The method used in this research was descriptive in the form of qualitative research. The data were analyzed qualitatively to determine the level of completeness by using a simple statistical method that was presented quantitatively. The findings showed that the planning in cycle I and II was in accordance with the process skill approach, however, the selected approach was not included in the lesson plan and thus revised in cycle II. The acting in cycle I was conducted well based on the APKG II assessment and was improved in cycle II. The learning outcomes resulted in improvement as seen on the test result in cycles I and II from 71,4 to 77,56. Therefore, the selected learning approach improved the students? learning outcomes in writing news texts. Keywords: Writing News Text, Process Skill Approach.